Pigeon Pea and Cowpea-Based Cropping Systems Improve Vesicular Arbuscular Mycorrhizal Fungal Colonisation of Subsequent Maize on the Alfisols in Central Malawi - Keston O. W. Njira; Ernest Semu; Jerome P. Mrema; Patson C. Nalivata (International Journal of Microbiology)
Mycorrhizal associations contribute to the sustainability of crop production systems through their roles in nutrient cycling and other benefits in the soil-plant ecosystems. A two-year study was conducted on the Alfisols of Lilongwe and Dowa districts, Central Malawi, to assess the vesicular-arbuscular mycorrhizal (VAM) fungal colonisation levels in pigeon pea, cowpea, and maize grown in sole cropping, legume-cereal, and legume-legume intercropping systems and in the maize grown in short rotation (year 2) as influenced by the previous cropping systems and N fertilizer application. The gridline intersect method was used to assess the VAM fungal colonisation levels. Results showed that all treatments that included legumes whether grown as sole crop, in legume-cereal or in legume-legume cropping systems in the previous year, had significantly higher (P < 0.05) VAM fungal colonisation of the rotational maize crop roots by a range 39% to 50% and 19% to 47% than those in maize supplied and not supplied with N fertilizer, respectively, in a maize-maize short rotation, at the Lilongwe site. A similar trend was reported for the Dowa site. Furthermore, there were positive correlations between VAM fungal colonisation and the plant P content, dry matter yield, and nodule numbers. Further studies may help to assess the diversity of VAM fungal species in Malawi soils and identify more adaptive ones for inoculation studies.